P-selectin glycoprotein ligand 1 promotes T cell lymphoma development and dissemination - Pereira, João L. (2021)
P-selectin glycoprotein ligand-1 (PSGL-1) is a membrane-bound glycoprotein expressed in lymphoid and myeloid cells. It is a ligand of P-, E- and L-selectin and is involved in T cell trafficking and homing to lymphoid tissues, among other functions. PSGL-1 expression has been implicated in different lymphoid malignancies, so here we aimed to evaluate the involvement of PSGL-1 in T cell lymphomagenesis and dissemination. PSGL-1 was highly expressed at the surface of human and mouse T cell leukemia and lymphoma cell lines. To assess its impact on T cell malignancies, we stably expressed human PSGL-1 (hPSGL-1) in a mouse thymic lymphoma cell line, which expresses low levels of endogenous PSGL-1 at the cell surface. hPSGL-1-expressing lymphoma cells developed subcutaneous tumors in athymic nude mice recipients faster than control empty vector or parental cells. Moreover, the kidneys, lungs and liver of tumor-bearing mice were infiltrated by hPSGL-1-expressing malignant T cells. To evaluate the role of PSGL-1 in lymphoma cell dissemination, we injected intravenously control and hPSGL 1-expressing lymphoma cells in athymic mice. Strikingly, PSGL-1 expression facilitated disease infiltration of the kidneys, as determined by histological analysis and anti-CD3 immunohistochemistry. Together, these results indicate that PSGL-1 expression promotes T cell lymphoma development and dissemination to different organs.